ANALISIS AKUNTANSI PERTANGGUNGJAWABAN DALAM PENILAIAN KINERJA PUSAT PENDAPATAN PADA PT POS INDONESIA (PERSERO) CABANG RAHA - Dewi Rizki; Ishak Awaluddin; Fitriaman (Jurusan Akuntansi, Universitas Halu Oleo, 2026)
This study aims to analyze the application of responsibility accounting in revenue center performance assessment at PT. Pos Indonesia Raha Branch. The research method used was descriptive qualitative, through data collection in the form of interviews, observation, and documentation. The results show that the implementation of responsibility accounting has been running quite well through a clear organizational structure, division of authority, and accountability reports. However, revenue realization in 2023 only reached 27.48% and in 2024 decreased to only 26.94% of the set target due to internal factors such as suboptimal marketing strategies, technological limitations, and external competition from digital courier services. Therefore, the responsibility accounting system at PT. Pos Indonesia's Raha Branch needs improvement through realistic budget planning, strict oversight, and more effective operational strategies.